Identification and Characterization of miRNAs in Response to Leishmania donovani Infection: Delineation of Their Roles in Macrophage Dysfunction - Tiwari, Neeraj; Kumar, Vinod; Gedda, Mallikarjuna Rao; Singh, Ashish K.; Singh, Vijay K.; Singh, Surya P.; Singh, Rakesh K. (Frontiers in Microbiology, 2017)
The outcome of Leishmania infection depends on parasite abilities to evade host immune response and its survival in hostile environment of host macrophages. Despite a wealth of gained crucial information, parasite strategies by which it dampens host macrophage functions remain poorly understood. Micro RNAs (miRNAs) are evolutionarily conserved class of endogenous 22-nucleotide small non-coding RNA gene products, described to participate in the regulation of almost every cellular process investigated so far. In this study, we identified 940 miRNAs in L. donovani infected macrophages by de novo sequencing out of which levels of 85 miRNAs were found to be consistently modified by parasite infection. Herein, we report the functional characteristics of 10 miRNAs i.e. mir-3620, mir-6385, mir-6973a, mir-6996, mir-328, mir-8113, mir-3473f, mir-763, mir-6540 and mir-1264 that were differentially but constantly regulated in infected macrophages for their role in regulation of macrophage effector functions. The target gene prediction and biological interaction analysis revealed involvement of these miRNAs in various biological processes such as apoptosis inhibition, phagocytosis, drug response, and T cell phenotypic transitions. These findings could contribute for the better understanding of macrophages dysfunction and leishmanial pathogenesis. Further, the identified miRNAs could also be used as biomarker/s in diagnosis, prognosis, and therapeutics of Leishmania infection.